If it's not what You are looking for type in the equation solver your own equation and let us solve it.
91x-8=11+12x(x+5)
We move all terms to the left:
91x-8-(11+12x(x+5))=0
We calculate terms in parentheses: -(11+12x(x+5)), so:We get rid of parentheses
11+12x(x+5)
determiningTheFunctionDomain 12x(x+5)+11
We multiply parentheses
12x^2+60x+11
Back to the equation:
-(12x^2+60x+11)
-12x^2+91x-60x-11-8=0
We add all the numbers together, and all the variables
-12x^2+31x-19=0
a = -12; b = 31; c = -19;
Δ = b2-4ac
Δ = 312-4·(-12)·(-19)
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{49}=7$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(31)-7}{2*-12}=\frac{-38}{-24} =1+7/12 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(31)+7}{2*-12}=\frac{-24}{-24} =1 $
| 12y+28+3y=18 | | 326+x=345 | | 7/20=1/6+1/2w | | 3xx=48 | | 54x=648 | | -6+-1c=-6-5 | | 36+8h=-6(-9h-6) | | 20+.2x=30 | | 2/3p-1/6=2/7 | | 4(3x+5)=15x+16-3x+4 | | (3y+9)²=81 | | 7(8-8n)=504 | | -26-6x=1+3(-2x-8) | | 7x-5=12+2(x+12) | | 2w+5=4(w-1) | | -3(2a-1)+2a=9 | | 0=(-x-1)^3 | | 1/6-1/3h=2/3 | | -2+-3y=-20 | | 4x(x-7)=-44 | | 3(x+4)+6=12x-9 | | 12x+9=2×-11 | | -2x+5x=-15+3 | | -2p+8=6-(9p+2)= | | u/8.96=7 | | -15v-28=-15v+12 | | 5/7+b/5=7/10 | | 6+-2b=4 | | 7x+10+10+x+x=180 | | 7x-5=10+12(x+5) | | -12x+20=80 | | 6+-2p=4 |